2021
DOI: 10.1136/bmjopen-2020-042081
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of robot-assisted training versus an enhanced upper limb therapy programme or usual care for patients with moderate or severe upper limb functional limitation due to stroke: results from the RATULS randomised controlled trial

Abstract: ObjectiveTo determine whether robot-assisted training is cost-effective compared with an enhanced upper limb therapy (EULT) programme or usual care.DesignEconomic evaluation within a randomised controlled trial.SettingFour National Health Service (NHS) centres in the UK: Queen’s Hospital, Barking, Havering and Redbridge University Hospitals NHS Trust; Northwick Park Hospital, London Northwest Healthcare NHS Trust; Queen Elizabeth University Hospital, NHS Greater Glasgow and Clyde; and North Tyneside General Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…A total of 23 records were assessed for eligibility, with 8 being excluded for different reasons (conference papers and studied diseases other than neurological disorders). Finally, 15 studies [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] were included in the systematic review and were appraised for quality ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 23 records were assessed for eligibility, with 8 being excluded for different reasons (conference papers and studied diseases other than neurological disorders). Finally, 15 studies [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] were included in the systematic review and were appraised for quality ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 15 studies with 1634 patients were included in this review (1108 individuals who experienced a stroke and 99 with a spinal cord injury for robotic studies; 367 people who experienced a stroke, 30 with multiple sclerosis and 30 with cerebral palsy for virtual reality studies). Ten papers were focused on robotics [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ] and five on virtual reality [ 28 , 29 , 30 , 31 , 32 ] ( Figure 2 ). The studies showed a greater predominance of men than women.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This outcome has been subsequently confirmed by Mehrholz et al who reviewed the literature on the efficacy of upper limb Robot-assisted Therapy (ulRT) in improving activities of daily living, arm function, and arm muscle strength (6). The efficacy (7)(8)(9)(10)(11), acceptability (12), safety (13), and cost-effectiveness (14) of ulRT in stroke patients are well-established in literature.…”
Section: Introductionmentioning
confidence: 81%